Property‐oriented basis sets for computation of atomization energies. Issue 30 (26th August 2021) - García, Victor; Zorrilla, David; Fernández, Manuel; Sánchez‐Márquez, Jesús
Abstract: The SBO4‐DZ(d, p)‐3G basis sets introduced in a previous paper have been modified to improve their performance in the calculation of the atomization energies of organic molecules (pure or substituted hydrocarbons). The first step was to explore the possibility of improving those basis sets by adding a second D shell. The scale factor for an additional "D‐3G" shell was first studied by minimizing the total energies. In a second step, the scale factor was calculated by optimizing atomization energies directly (instead total energies). This way the results obtained were very similar to those of the cc‐pV5Z basis sets. Finally, we optimized simplified box orbital (SBO) basis sets for different methods obtaining optimal SBO basis sets for HF, DFTs, and MP2.